ANALYSIS OF TOURISM REMAINING WASTE MANAGEMENT ON THE HEALTH OF COASTAL COMMUNITIES IN LEPPE VILLAGE, SOROPIA DISTRICT, KONAWE REGENCY IN 2026 - Astrid Pratiwi Lahata; Ruslan Majid; Yasnani Yasnani (Media Inovasi Pendidikan dan Publikasi, 2026)
The tourism sector is a sector that makes a significant contribution to the economy, both at the local and national levels. However, the rapid development of the tourism industry is often accompanied by an increase in waste, including domestic liquid waste from hotel activities, restaurants, and residential areas around tourist areas. According to data from the WHO (2023), the tourism sector worldwide produces significant waste, contributing to the global waste pile reaching more than 11 million tons annually. This waste includes various types, including plastic and food waste, which have serious impacts on environmental health and the local economy. This study aims to analyze the management of residual tourism waste on the health of coastal communities in Leppe Village, Soropia District, Konawe Regency in 2026. This study uses a descriptive qualitative approach. The research instrument used a questionnaire. The results show that residual tourism waste in the coastal area of ​​​​Leppe Village is still found and has not been properly managed, both in terms of its presence and volume, which tends to increase with tourism activities. Waste management has not been carried out systematically and sustainably, characterized by the absence of sorting, limited facilities, and the practice of dumping and burning waste without processing. This situation indicates that the implementation of the 3R principles is not yet optimal and has the potential to degrade the quality of the coastal environment and negatively impact public health.